Post-stroke dyskinesias - Nakawah MO; Lai EC (Neuropsychiatric Disease and Treatment)
Mohammad Obadah Nakawah, Eugene C Lai Stanely H. Appel Department of Neurology, Houston Methodist Neurological Institute, Houston, TX, USA Abstract: Strokes, whether ischemic or hemorrhagic, are among the most common causes of secondary movement disorders in elderly patients. Stroke-related (vascular) movement disorders, however, are uncommon complications of this relatively common disease. The spectrum of post-stroke movement disorders is broad and includes both hypo- and hyperkinetic syndromes. Post-stroke dyskinesias are involuntary hyperkinetic movements arising from cerebrovascular insults and often present with mixed phenotypes of hyperkinesia which can sometimes be difficult to classify. Nevertheless, identification of the most relevant motor phenotype, whenever possible, allows for a more specific phenomenological categorization of the dyskinesia and thus helps guide its treatment. Fortunately, post-stroke dyskinesias are usually self-limiting and resolve within 6 to 12 months of onset, but a short-term pharmacotherapy might sometimes be required for symptom control. Functional neurosurgical interventions targeting the motor thalamus or globus pallidus interna might be considered for patients with severe, disabling, and persistent dyskinesias (arbitrarily defined as duration longer than 12 months). Keywords: vascular dyskinesia, stroke, movement disorders